2019
DOI: 10.1002/ijc.32314
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in metabolite profile are associated with risk of more aggressive prostate cancer: A prospective study of 3,057 matched case–control sets from EPIC

Abstract: Metabolomics may reveal novel insights into the etiology of prostate cancer, for which few risk factors are established. We investigated the association between patterns in baseline plasma metabolite profile and subsequent prostate cancer risk, using data from 3,057 matched case–control sets from the European Prospective Investigation into Cancer and Nutrition (EPIC). We measured 119 metabolite concentrations in plasma samples, collected on average 9.4 years before diagnosis, by mass spectrometry (AbsoluteIDQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 45 publications
3
70
2
Order By: Relevance
“…The positive association between LPC C18:0 and risk of overall prostate cancer (Table 3) in the present study was not observed in any of the EPIC-multicentre studies (ORs close to one) [13,15]. In the EPIC-Heidelberg study, an inverse association between LPC C18:0 and overall prostate cancer risk (p < 0.05) was observed, but the association was no longer significant after correction for multiple testing or adjusting for confounding factors in that case-cohort study [10].…”
Section: Other Studiescontrasting
confidence: 47%
See 3 more Smart Citations
“…The positive association between LPC C18:0 and risk of overall prostate cancer (Table 3) in the present study was not observed in any of the EPIC-multicentre studies (ORs close to one) [13,15]. In the EPIC-Heidelberg study, an inverse association between LPC C18:0 and overall prostate cancer risk (p < 0.05) was observed, but the association was no longer significant after correction for multiple testing or adjusting for confounding factors in that case-cohort study [10].…”
Section: Other Studiescontrasting
confidence: 47%
“…Seven previous studies have investigated the association between metabolite levels and the risk of prostate cancer incidence in prospectively collected human blood samples [9][10][11][12][13][14][15]. Three of these studies were nested within the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study (ATBC) [11,12,14]; one within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) [9]; one within the European Prospective Investigation into Cancer and Nutrition study (EPIC) in Heidelberg [10]; and two within the EPIC-multicentre cohort (Germany, Greece, Italy, the Netherlands, Spain and the UK) [13,15]. The ABTC and PLCO studies used untargeted metabolomics to non-quantitatively measure many metabolites, many not targeted in the present study.…”
Section: Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic profiling of tissues and biofluids including blood plasma [80][81][82][83], urine [84][85][86], and cerebrospinal fluid (CSF) [86][87][88][89] using NMR and MS in the past decade has been shown to be very valuable for reporting disease states and drug responses. This is due to metabolic reprogramming in • C/5% CO 2 before fixing in 4% buffered formalin, embedded in paraffin block, and sectioned into 4 µm slices for H&E staining in (A) and IF staining for cancer cells (panCytokeratin or panCK), CD8 (cytotoxic T cells), and CD68 (Mφ) in (B).…”
Section: Stable Isotope Resolved Metabolomics (Sirm)mentioning
confidence: 99%